From villains to victims: experiencing illness in Siberian exile - Badcock, Sarah (Taylor & Francis, 2013)
This essay presents the subjective experience of life and sickness for the punished in late Imperial Siberia, and the distinctions the punished made between legitimate and illegitimate forms of punishment. The essay also explores state policies towards the sick punished, and explores how different levels of the Tsarist administration and local Siberian society dealt with the challenge of sick and decrepit exiles. It argues that conditions in Siberian prisons were, in general, worse than those in European Russian prisons in the post-1906 period, and that the experience of exile in eastern Siberia placed it among the most difficult locations for exile. Though neither the state nor the punished regarded illness as an integral part of their punishment, the prevalence of illness and disease compounded the cruelty of sentences.